Multiple sclerosis: 2023 update - Kuhlmann, Tanja; Antel, Jack (Free Neuropathology, 2023)
Multiple sclerosis (MS) is the most frequent inflammatory and demyelinating disease of the Central Nervous System (CNS). Significant progress has been made during recent years in preventing relapses by using systemic immunomodulatory or immunosuppressive therapies. However, the limited effectiveness of such therapies for controlling the progressive disease course indicates there is a continuous disease progression independent of relapse activity which may start very early during the disease course. Dissecting the underlying mechanisms and developing therapies for preventing or stopping this disease progression represent, currently, the biggest challenges in the field of MS. Here, we summarize publications of 2022 which provide insight into susceptibility to MS, the basis of disease progression and features of relatively recently recognized distinct forms of inflammatory/demyelinating disorders of the CNS, such as myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD).